LITERASI KEUANGAN UMKM DALAM MENGHADAPI ERA SOCIETY 5.0 DI KABUPATEN BOALEMO PROVINSI GORONTALO - Sukrianto Sukrianto; Fibriyanti S Lakoro (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to analyze and determine the ability of SMEs to financial literacy in facing the Era of Society 5.0 in Boalemo Regency. The research method used is descriptive qualitative research. Research informants are MSME actors and the Department of Cooperatives, MSMEs, Industry and Trade of Boalemo Regency. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is an interactive model through data reduction, data presentation and inference or verification. The results of the study indicate that MSME financial literacy in facing the Era of Society 5.0 in Boalemo Regency has begun to be implemented in several MSMEs. It's just that the biggest drawback is more detailed knowledge related to MSME financial literacy in facing the Era of Society 5.0. For the understanding of financial literacy in MSMEs is good, even the competence of many MSMEs is aware of MSME financial literacy in facing the Era of Society 5.0. However, the awareness and risk of financial literacy are considered not in accordance with the conditions because there are still some MSMEs who are not literate and unable to develop financial literacy. Responsibilities have been carried out, especially in reporting, taxes and others.